Shrek and Media Literacy: Five Kurdish Young Women’s Perspectives - Abdulqadr, Kezhan Salar (Technium Social Sciences Journal, 2020)
This study explored how five young Kurdish women perceived the concepts of beauty, self-acceptance, and "princess" in American popular culture through interpretations of the messages from the movie series Shrek. The data were collected through one-on-one interviews via webcam with five young Kurdish women living in Kurdistan and the United Kingdom. The interviews were conducted in the Kurdish language, audiotape-recorded, transcribed, and then translated into the English language. Data analysis focused on comparing the five young women’s responses to the interview questions. The results of the study showed that these three issues were interrelated with one another. All five participants believed that one’s inner beauty was more important than physical beauty because it would lead a female to accept herself, which, in turn, led to her happiness and being accepted by others. Also, a beautiful soul and self-acceptance were required in a modern princess who should be brave and independent. Inspired by Fiona in the film, the five young women have learned to accept themselves more, think more wisely about their choices in life, and fight for their freedom, if necessary.